Deep Brain Stimulation in Patients with Parkinson's Disease: Effect on Psychiatric Symptoms and Quality of Life - Seijo Zazo, Elisa; Fernandez, Fernando Seijo; Liebana, Elena Santamarta; Ayala, Antonio Saiz; Aragoneses, Beatriz Lozano; Campa, Jose Maria Torres; Portilla, Paz Garcia; Vega, Marco Alvarez (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims To determine the effect on psychiatric symptoms and quality of life in 30 patients with Parkinson's disease (PD) treated with deep brain stimulation (DBS) of both subthalamic nuclei (STN) after 1 year of follow-up.Material and Method We conducted a prospective 1-year follow-up study with a baseline assessment before and 6 and 12 months after surgery. The following were used as assessment instruments: the Bech-Rafaelsen Melancholia Scale (MES), the Bech-Rafaelsen Mania Scale (MAS), the Beck Scale for Suicidal Ideation (SSI), the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), the Oviedo Sleep Questionnaire (OSQ), the 36-Item Short Form Health Survey (SF-36), the Unified Parkinson's Disease Rating Scale (UPDRS), the dose of levodopa, and the active contact stereotactic coordinates.Results We recorded a clinical improvement between baseline with medication use (ON medication) and the results obtained at 6 and 12 months with medication use and stimulation (ON stimulation, ON medication) in MES and OSQ (p < 0.0001) and in SF-36 (p < 0.005). No changes were observed in MAS and SSI. There was a clinical improvement between baseline with ON medication and the results obtained at 12 months with ON stimulation, ON medication in Y-BOCS (p < 0.04). Also, there was a 53.3% reduction in levodopa at 6 months and a 54.7% reduction at 12 months after surgery (p < 0.0001). There was an improvement between baseline with OFF medication and the results obtained at 6 and 12 months OFF medication, ON stimulation (p < 0.0001) in UPDRS-III. There were no statistically significant differences between the initial and final active contact coordinates, or between stimulation parameters.Conclusions DBS of the STN in patients with PD is associated with an improvement in psychiatric (affective and sleep-wake cycle) symptoms, clinical motor symptoms, and quality of life at 1 year after surgery.
Keywords: Parkinson's disease; psychiatric symptoms; quality of life; deep brain stimulation